Effects of an educational intervention to strengthen humanistic practice on haemodialysis nurses' caring attitudes and behaviours and quality of working life: a cluster randomised controlled trial - Matteo Antonini; Tanja Bellier-Teichmann; Louise O'reilly; Chantal Cara; Sylvain Brousseau; Jean Weidmann; Delphine Roulet-Schwab; Isabelle Ledoux; Mario Konishi; Jérôme Pasquier; Philippe Delmas (BMC, 2021)
Abstract Background Nurses are trained to establish a trusting relationship with patients to create an environment promoting patients' quality of life. However, in tech-heavy care settings, such as haemodialysis units, dehumanising practices may emerge and take root for various reasons to the potential detriment of both patients and nurses. For patients, this may lead to a deterioration of quality of life and, ultimately, of health status. For nurses, it may cause a deterioration of the work environment and, in turn, of quality of working life. Based on Watson's Theory of Human Caring, we developed a brief educational intervention for haemodialysis nurses to strengthen their humanistic practice in the aim of improving the nurse-patient relationship and nurse quality of working life.. The intervention was tested by way of an experimental design. Methods One hundred and one haemodialysis nurses, recruited in ten hospitals in French-speaking Switzerland, were randomised into an experimental group that received the intervention and a control group. The nurse-patient relationship was measured with the Caring Nurse-Patient Interaction Scale (EIIP-70) and nurse quality of life at work was measured with the Quality of Work Life Questionnaire at four time points: pre-intervention, intervention completion, and six-month and one-year follow-ups. Random intercept regression analysis was used to evaluate change over time in the two variables under study. Results The intervention appeared to reinforce nurse attitudes and behaviours geared to a more humanistic practice. The effect seemed to fade over time but, 1 year post-intervention, six dimensions of the nurse-patient relationship (hope, sensibility, helping relationship, expression of emotions, problem solving, teaching) scored above baseline. Nurse quality of working life, too, seemed positively impacted. The cultural dimension of nurse quality of working life, that is, the degree to which everyday work activities attune with personal and cultural values, seemed positively impacted, as well, with improvement stable throughout the year following the intervention. Conclusions Results support a positive effect of the intervention over both the short term and the medium-to-long term. A brief intervention of the sort may constitute an effective means to improve the nurse-patient relationship by preventing or reducing dehumanising practices. Trial registration NCT03283891 .